2015
DOI: 10.1097/opx.0000000000000551
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Waggoner Computerized Color Vision Test

Abstract: The Waggoner CCVT is an adequate color vision screening test with several advantages and appears to provide a fairly accurate diagnosis of deficiency type. Used in conjunction with other color vision tests, it may be a useful addition to a color vision test battery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…This selection could have effectively separated normal trichromats from the colour vision deficient 2012. Earlier studies comparing smartphone‐based applications to Ishihara's booklet have demonstrated a good sensitivity and specificity with few applications (Eye2Phone)2015 and a relatively poor specificity (colour vision test) with few other applications 2016. This difference was attributed to the technologies involved like the property of display, screen size and corresponding test plate size, glare and reflections from the smartphone screen.…”
Section: Discussionmentioning
confidence: 99%
“…This selection could have effectively separated normal trichromats from the colour vision deficient 2012. Earlier studies comparing smartphone‐based applications to Ishihara's booklet have demonstrated a good sensitivity and specificity with few applications (Eye2Phone)2015 and a relatively poor specificity (colour vision test) with few other applications 2016. This difference was attributed to the technologies involved like the property of display, screen size and corresponding test plate size, glare and reflections from the smartphone screen.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects who were identified as colour vision deficient during the Pre-testing phase were excluded from the analysis. Both tests were third party validated and are amongst current tools recommended by FAA and EASA for aircrew colour vision assessment [ 5 , 32 , 36 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…As the Ishihara test focuses on the diagnosis of congenital red-green abnormality, we selected a specific test plate from the WCCVT for the diagnosis of tritanomalous CDO. It is worth noting that the WCCVT's Adult Diagnostic test is highly regarded and has been selected as one of three "precision" color vision tests available by the U.S.FAA [2]. The diagnostic test for WCCVT is capable of identifying tritanomalous CDO.…”
Section: Test Plate Selectionmentioning
confidence: 99%
“…However, there are differences between computerized and paper-based testing result. For example, the screening performance of the computerized color vision test (CCVT) is similar to other PIP tests, but the diagnostic performance differs [2]. The W-D15 and F-D15 tests do not exhibit perfect consistency [3].…”
Section: Introductionmentioning
confidence: 99%